O reinocentrismo de Jesus como chave para uma cristologia no pluralismo religioso - Lima, Adriano Sousa (2013)
This dissertation reflects on the theme The Kingdom of God as key to a Christology in religious pluralism. We seek to determine as much as the Kingdom of God can be a key hermeneutical Christology in favor of religious pluralism. To support this point, we have come through a literature review the thinking of some theologians of the systematic area, as well as theologians of the biblical area. In the first chapter, we introduce the concept of culture, we developed the idea of cultural diversity including Brazil and affirm pluralism as a cultural factor. In the second chapter, from the reflection on the hermeneutic turn and the presentation of some theological paradigms, we founded religious pluralism as a paradigm of theology, which Christian reflection cannot escape. In the third and final chapter, the focus of the category Kingdom of God and its centrality in the life of Jesus of Nazareth was essential to affirm the possibility of a Christology in religious pluralism.